Cyclic response of RC beam-column joints reinforced with plain bars: an experimental testing campaign - Melo, J. (2012)
Existing reinforced concrete (RC) buildings constructed until the mid-70’s, with plain reinforcing bars, are expected to behave poorly when subjected to earthquake actions. This paper describes an experimental program designed to investigate the influence of poor detailing on the cyclic behaviour of RC beam-column joint elements. Cyclic tests were performed on five interior and five exterior full-scale beam-column joints with different detailing characteristics and reinforced with plain bars. An additional joint of each type was built with deformed bars for an evaluation of the influence of bond properties on the cyclic response of the structural element. The force-displacement global response, energy dissipation, equivalent damping and damage behaviour of the joints was investigated and the main results are presented and discussed. The experimental results indicate that the bond-slip mechanism has significantly influenced the cyclic response of the beam-column joints. The specimens built with plain bars showed lower energy dissipation, stiffness and equivalent damping.